Phenotypic detection of broad-spectrum beta-lactamases in microbiological practice - Htoutou Sedlakova, Miroslava; Hanulik, Vojtech; Chroma, Magdalena; Hricova, Kristyna; Kolar, Milan; Latal, Tomas; Schaumann, Reiner; Rodloff, Arne C (Medical science monitor, 2011)
BACKGROUND: Enterobacteriaceae producing ESBL and AmpC enzymes can be associated with failure of antibiotic therapy and related morbidity and mortality. Their routine detection in microbiology laboratories is still a problem. The aim of this study was to compare the sensitivity of selected phenotypic methods. MATERIAL/METHODS: A total of 106 strains of the Enterobacteriaceae family were tested, in which molecular biology methods confirmed the presence of genes encoding ESBL or AmpC. In ESBL-positive strains, the sensitivity of the ESBL Etest (AB Biodisk) and a modified double-disk synergy test (DDST) were evaluated. AmpC strains were tested by a modified AmpC disk method using 3-aminophenylboronic acid. For simultaneous detection of ESBL and AmpC, the microdilution method with a modified set of antimicrobial agents was used. RESULTS: The sensitivity of the ESBL Etest was 95%; the modified DDST yielded 100% sensitivity for ESBL producers and the AmpC test correctly detected 95% of AmpC-positive strains. The sensitivity of the modified microdilution method was 87% and 95% for ESBL and AmpC beta lactamases, respectively. CONCLUSIONS: The detection of ESBL and AmpC beta lactamases should be based on specific phenotypic methods such as the modified DDST, ESBL Etest, AmpC disk test and the modified microdilution method.
Keywords: Microbial Sensitivity Tests; Bacterial Proteins; Reference Standards; beta-Lactamases; beta-laktamasy; Klebsiella pneumoniae; Sensitivity and Specificity; mikrobiální testy citlivosti; senzitivita a specificita; Anti-Infective Agents; Phenotype; antiinfekční látky; referenční standardy; cefalosporiny; fenotyp; Cephalosporins; Enterobacteriaceae; bakteriální proteiny